2018
DOI: 10.1021/acs.bioconjchem.8b00843
|View full text |Cite
|
Sign up to set email alerts
|

Natural Product Bis-Intercalator Depsipeptides as a New Class of Payloads for Antibody–Drug Conjugates

Abstract: A potent class of DNA-damaging agents, natural product bis-intercalator depsipeptides (NPBIDs), was evaluated as ultrapotent payloads for use in antibody–drug conjugates (ADCs). Detailed investigation of potency (both in cells and via biophysical characterization of DNA binding), chemical tractability, and in vitro and in vivo stability of the compounds in this class eliminated a number of potential candidates, greatly reducing the complexity and resources required for conjugate preparation and evaluation. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…Late-stage introduction of the methylthio group also allowed us to easily access a range of analogues modified at the methylthio moiety. Compound 23 could be used as an intermediate for a chemical probe or an antibody−drug conjugate 28 because it has a handle for linking to a variety of functional molecules. This strategy can be applicable to a range of echinomycin analogues.…”
mentioning
confidence: 99%
“…Late-stage introduction of the methylthio group also allowed us to easily access a range of analogues modified at the methylthio moiety. Compound 23 could be used as an intermediate for a chemical probe or an antibody−drug conjugate 28 because it has a handle for linking to a variety of functional molecules. This strategy can be applicable to a range of echinomycin analogues.…”
mentioning
confidence: 99%
“…In 2019, Ratnayake et al (Pfizer) developed a series of HER2-targeting ADCs bearing depsipeptides, an extremely potent class of cytotoxins, at different attachment sites. 287 The lead conjugate PF-06888667, comprising the depsipeptide SW-163D conjugated via a cleavable AcLys-Val-Cit-PABC-DMAE (dimethylethylenediamine) linker, exhibited subnanomolar in vitro cytotoxicity against N87 and MDA-MB-361-DYT2 cell lines. Complete tumour regression was observed in an N87 xenograft mouse model at a dosage ten-fold lower than that of the approved T-DM1.…”
Section: Transglutaminasementioning
confidence: 99%
“…Other important DNA damaging agents currently used as payloads in clinical trials are duocarmycins e and pyrrolobenzodiazepines (PBD, d); they have unique, well-understood minor groove binding mechanisms that disrupt normal DNA function leading to cell death. Novel payloads have been explored recently in this space such as bis-intercalator depsipeptides with nanomolar affinity to DNA [99]. Pfizer demonstrated that this ultra-potent payload a (Figure 4) can overcome the previous limits of efficacy in animal models, therefore, expanding their relevance to indications beyond liquid tumors.…”
Section: Current Small Molecule Payloads and Beyondmentioning
confidence: 99%